ULTIMATE ELONGATION OF CONCRETE (Academic journal Industrial Machine Building Civil Engineering, 2017)
It is shown the results of experimental studies of the deformation and concrete fracture process under the axial tension and under the conditions of non-homogeneous state of stress when changing the deformation gradient over the cross section. The test samples were loaded by the short duration load to the point of structural and with load alleviation under the stresses close to destruction. The basic influencing factors on the ultimate elongation of studied types of concrete are found out and the analytical dependences for their description are proposed. The experiments have shown that under the non-uniform stress state the ultimate elongation is not constant; it varies within a wide range and depends on the critical strain gradient. For solving applied problems, the suitable, for practical use, universal form of connection load – deformation was offered, which truly reflects the unity of the relation between stress and deformation of concrete, which is in the condition of homogeneous and non-homogeneous stress states.
Keywords: stress-strain diagram of cracked concrete; ultimate elongation of concrete; axial tension; the deformation gradient